The role of microRNAs in regulating neuronal connectivity - Chiu, Hui; Alqadah, Amel; Chang, Chieh (Frontiers in Cellular Neuroscience, 2014)
The assembly of functional neural circuits is critical for complex thoughts, behavior and general brain function. Precise construction of neural circuits requires orderly transition of sequential events from axon outgrowth, pathfinding, branching, to synaptogenesis. Each of these steps is required to be tightly regulated in order to achieve meticulous formation of neuronal connections. MicroRNAs (miRNAs), which silence gene expression post-transcriptionally via either inhibition of translation or destabilization of messenger RNAs, have emerged as key regulators of neuronal connectivity. The expression of miRNAs in neurons is often temporally and spatially regulated, providing critical timing and local mechanisms that prime neuronal growth cones for dynamic responses to extrinsic cues. Here we summarize recent findings of miRNA regulation of neuronal connectivity in a variety of experimental platforms.